Comparing Mortgage Financing Marketing Strategies: Conventional Bank vs Sharia Bank - Elisa, Nur; Rahmawati, Rafika; Putra, Purnama (Research of Islamic Economics, 2024)
The increasingly diverse needs of society have made financing the most popular banking service product. KPR products certainly require a marketing strategy. One of the interesting products offered by BRI Syariah Tambun Sub-Branch Office (KCP) is the Home Ownership Financing/Mortgage (KPR) product. This research aims to determine the marketing strategy for Mortgage Financing (KPR) between two banks, namely Conventional Banks and Sharia Banks at Bank BRI KCP Tambun and BRISyariah KCP Tambun. The data sources used are primary and secondary. Data collection was carried out using interview and documentation techniques. The results of this research show that KPR products at Bank BRI and BRI Syariah, in their implementation, apply similar marketing strategies. At Bank BRI, in implementing its marketing strategy, it takes a conventional approach by referring to the strategy of providing interest and using a credit approach with low interest; it places more emphasis on KPR marketing strategies, which tend to prioritize Islamic principles. Managerial implications emerge from the comparative analysis, shedding light on the strengths and weaknesses of each approach.